Causal Inference Analysis for Poorly Soluble Low Toxicity Particles, Lung Function, and Malignancy - Harber, Philip (Frontiers in Public Health, 2022)
Poorly soluble low toxicity (PSLT) particles have raised concern about possible nonmalignant and malignant pulmonary effects. PSLT’s include carbon black, titanium dioxide, and other agents. This paper applies formal causal inference analysis to assessing these effects. Methods: A framework for analysis is created using directed acyclic graphs to define pathways from exposure to potential lung cancer or obstructive airway disease outcomes. Observational predictive epidemiologic studies have limited ability to address poorly observable mechanistic steps. Mechanistic pathways include pulmonary inflammation as an intermediate step. Next, an overview of available data for each of the inter-node links is presented. Gaps in the available data from epidemiologic, laboratory toxicology, and clinical studies are delineated. Potential influences of confounders, backdoor pathways, and analytic models are presented graphically. Results: Individual empirical studies are unlikely to confirm mechanisms of potential causal relationships due to the complexity of causal pathways. However, explicit networks permit combining data from disparate research study methods to objectively assess pulmonary inflammation is a common pathway for both obstructive airway disease and lung cancer. This analysis also has potential to overcome limitations of traditional epidemiologic methods for these long latency health outcomes. These methods are useful to clarify potential bona fide and artefactual observed relationships.